EFEKTIVITAS INSTRUMEN HUKUM DALAM ELECTRICITY DIRECTIVE 72/2009/EC - Piter Zunimik Sinaga (Jurnal Paradigma Hukum Pembangunan, 2019)
In order to achieve effective competition needs several instruments that are expected to facilitate the achievement of these goals. Electricity Directive[1] provides a new system and some renewal of existing systems. The application of such instruments shall fulfill the fundamental principles. The question may arises, how far these instruments are able to ensure effective competition and its application synergy between instruments. This paper will seeks to addresses the question of by which instruments of the Electricity Directive does the EU ensure competition in the electricity sector, in order to analyses whether all the instruments are sufficient to ensure effective competition this paper also will discusses the benefits and deficits of those instruments. In the first part of this paper general information about the essential idea behind Electricity Directive, the main instruments with their benefits and deficits will be discussed in the following parts respectively. The conclusion part answers the question whether all the instruments are sufficient to ensure effective competition or not.